Structural Response Analysis of a Fiber-Reinforced Composite Horizontal Axis Tidal Turbine Blade using Blade Element Momentum-Derived Blade Loading - Callanga, Jennifer; Danao, Louis Angelo; Abuan, Binoe (Philippine Engineering Journal, 2023)
The structural integrity of the newly designed rotor of a horizontal axis turbine blade was tested for structural response due to hydrodynamic loading. A verification and validation study using elliptical tube with isotropic material properties was conducted first to assess the accuracy of the numerical model. Further study involving the actual blade configuration with a spar was simulated using both orthotropic material properties of glass fiber reinforced polymer (GFRP) and carbon fiber reinforced polymer (CFRP) composites. A parametric study of ply angle and blade shell thickness was conducted to determine appropriate geometric configurations that will yield the lowest maximum principal stress and blade deformation. It was observed that the maximum principal stress is 154.44 MPa and the tip deflection is 139.66 mm for GFRP and 141.83 MPa with tip deflection of 68.26 mm for CFRP for shell thickness equivalent to 2% of the maximum blade chord length and a ply angle of 0°. When the ply angle is increased, the maximum principal stress increases with the worst condition at a ply angle of 45°. Shell thickness was studied, and results show that increasing the thickness decreased the maximum principal stress. When the shell thickness is increased to 8% of the maximum blade chord, the recorded maximum principal stress and tip deflection similarly decrease. It is determined that the present rotor blade is an improved design with good overall hydrodynamic performance and low stress and deformation levels. Keywords — Momentum, Composite, Finite Elements, Horizontal Axis, Tidal Turbine